(untitled) (Research, Society and Development, 2021)
The COVID-19 pandemic is a milestone in Brazilian education when one observes the time in which the country’s schools are closed due to the social distancing, necessary to cope with the pandemic. It was necessary, therefore, an upload from the physical school to cyberspace, in a sudden and traumatic way. Although it is not possible to generalize the school model that will be established at the post-pandemic moment, it is a fact that physical school, at a time before the pandemic, was being modified by the advent of cyberculture and network education. Therefore, this work aims to evaluate the concepts of blended learning and artificial intelligence in the context of network education, considering cyberspace as the support for virtual school. As a research methodology, we opted for a literature review including the main authors who discuss the themes under analysis and Social Network Analysis (SNA) for Twitter and YouTube under the themes in analysis. It is concluded that, in the post pandemic, it is likely that the physical school complements the virtual school, in a process of synchrony and connection which will not be possible to distinguish one from the other, where network education will guide teaching practices and student’s practices also.